Boks w kadrze. Wybrane strategie inscenizacyjne w polskich filmach o boksie z lat sześćdziesiątych i siedemdziesiątych XX wieku - Wierski, Dominik (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2020)
In his article, Dominik Wierski analyses and interprets selected staging strategies in Polish films about boxing. The films cited in the text were made in the 1960s and 1970s. It was a dynamic period in Polish cinematography, but also a great time for Polish boxing. The author wonders how filmmakers showed space related to boxing - training rooms, changing rooms, stands and the boxing ring. Selected films, belonging to the most important examples of Polish filmmakers’ insight into the world of boxing, are analyzed in the terms of their use of colors, sound, camera travel, rhythm and pace etc. The purpose of the text is to answer the question of whether Polish films of the ‘60s and ‘70s developed an integral way of discussing boxing and showing its most characteristic spaces.